15q11-13 GABAA receptor genes are normally biallelically expressed in brain yet are subject to epigenetic dysregulation in autism-spectrum disorders - Hogart, Amber; Nagarajan, Raman P.; Patzel, Katherine A.; Yasui, Dag H.; LaSalle, Janine M. (Human molecular genetics, 2007)
Human chromosome 15q11-13 is a complex locus containing imprinted genes as well as a cluster of three GABAA receptor subunit (GABR) genes—GABRB3, GABRA5 and GABRG3. Deletion or duplication of 15q11-13 GABR genes occurs in multiple human neurodevelopmental disorders including Prader-Willi syndrome (PWS), Angelman syndrome (AS) and autism. GABRB3 protein expression is also reduced in Rett syndrome (RTT), caused by mutations in MECP2 on Xq28. Although Gabrb3 is biallelically expressed in mouse brain, conflicting data exist regarding the imprinting status of the 15q11-13 GABR genes in humans. Using coding single nucleotide polymorphisms we show that all three GABR genes are biallelically expressed in 21 control brain samples, demonstrating that these genes are not imprinted in normal human cortex. Interestingly, four of eight autism and one of five RTT brain samples showed monoallelic or highly skewed allelic expression of one or more GABR gene, suggesting that epigenetic dysregulation of these genes is common to both disorders. Quantitative real-time RT–PCR analysis of PWS and AS samples with paternal and maternal 15q11-13 deletions revealed a paternal expression bias of GABRB3, while RTT brain samples showed a significant reduction in GABRB3 and UBE3A. Chromatin immunoprecipitation and bisulfite sequencing in SH-SY5Y neuroblastoma cells demonstrated that MeCP2 binds to methylated CpG sites within GABRB3. Our previous studies demonstrated that homologous 15q11-13 pairing in neurons was dependent on MeCP2 and was disrupted in RTT and autism cortex. Combined, these results suggest that MeCP2 acts as a chromatin organizer for optimal expression of both alleles of GABRB3 in neurons.